Copper(II)-Bis-Cyclen Intercalated Graphene Oxide as an Efficient Two-Dimensional Nanocomposite Material for Copper-Catalyzed Azide–Alkyne Cycloaddition Reaction - Samuel, Angel Green; Subramanian, Sowmya; Vijendran, Vijaikanth; Bhagavathsingh, Jebasingh (Frontiers in Chemistry, 2022)
We report the stable and heterogeneous Graphene oxide (GO) intercalated copper as an efficient catalyst for the organic transformations in green solvents. The GO intercalated copper(II) complex of bis(1,4,7,10-tetraazacyclododecane), [Cu(II)-Bis-cyclen] complex was prepared by the facile synthetic approach with the high dilution technique. The as-prepared GO-Cu(II)-Bis-cyclen nanocomposite was used as a click catalyst for the 1,3 dipolar Huisgen cycloaddition reaction of terminal alkyne and azide substrates. On directing the great zeal of attention towards the feasibility of the rapid electron transfer rate of the catalyst in proliferating the yield of 1,2,3- triazole products, the click catalyst GO-Cu(II)-Bis-cyclen nanocomposite was designed and synthesized via non-covalent functionalization. The higher coordination site of an efficient 2D nanocomposite facilitates the stabilization of Cu(I)L-acetylide intermediate in the catalytic cycle initiated by the addition of reductant. The XRD analysis shows the enhanced d-interlayers spacing of 1.04 nm due to the intercalation of Cu(II)-Bis-cyclen complex in between the GO basal planes. It was also characterized by XPS, FT-IR, RAMAN, UV, SEM, AFM and TGA techniques. The recyclability of the heterogeneous catalyst (GO-Cu(II)-Cyclen) with solvent effect have also been studied. This class of GO-Cu(II)-Bis-cyclen nanocomposite paves the way for bioconjugation of macromolecules through click chemistry approach.